Quantitative Estimation of Indices of Harms of Radiation and Other Environmental Agents and Comparison of Estimated Indices - YOSHIZAWA, Yasuo; BAN, Nobuhiko; KUSAMA, Tomoko (Hoken butsuri, 1989)
We investigated an appropriate “Index of Harm” for expressing risk of the public from viewpoints of radiation protection and acceptability of radiation risks of members of public. “Time loss of life” was selected as quantitative expression of Indices of Harm of radiation and other agents in environment. The “time loss of life” was able to express all objective health detriments of both radiation and other agents, and almost all members of public can easily understand this index. In this study, we estimated the “time loss of life” from radiation, trihalomethane in drinking-water and asbestos exposures at level of each dose limit. The “time loss of life” from radiation, trihalomethane and asbestos were estimated 7 days, 4 days and 0.1 day in male, and 13 days, 5 days and 0.1 day in female, respectively. An intercomparison of these three harms found that radiation had a slight higher “time loss of life” than other two agents. There are many uncertainties in the assessment of indices of harm of other agents, then, further investigations are needed.